Spatiotemporal analysis of decoupling urban expansion and carbon emissions in China: insights from different expansion and decoupling patterns - Lin, Xiangming; Liao, Yuantao; Wang, Shaojian (Frontiers in Environmental Science, 2025)
As urbanization accelerates, decoupling urban development from environmental consumption, particularly carbon emissions, is crucial for sustainable growth and achieving carbon neutrality goals. This study introduces urban expansion intensity as a new perspective to analyze the decoupling between urban expansion and carbon emissions. Based on the Urban Expansion Disparity Index, 297 Chinese cities are classified. The Tapio model is used to examine the spatiotemporal variations in decoupling from 2007 to 2022, while the LMDI model identifies key factors influencing regional carbon emissions. Findings reveal: (1) a polarized decoupling pattern, dominated by weak and strong negative decoupling; (2) a strong link between urban expansion types and decoupling modes, with fast-expanding cities exhibiting weak/strong decoupling and growth linkage, while slow-expanding or shrinking cities show expansion-negative and strong negative decoupling; (3) expansion and affluence effects drive emissions, while technology mitigates them, with significant regional differences. This study provides theoretical insights into urban expansion and carbon decoupling dynamics, informing region-specific policy interventions.